Determination of Lithium, Gallium, Zirconium, Rare Earth Elements and Other Trace Elements in Corundum-bearing Bauxite by Inductively Coupled Plasma-Mass Spectrometry with Rapid Decomposition of Ammonium Bifluoride - LIU Gui-lei; XU Chun-xue; CHEN Zong-ding; WEN Hong-li (Yankuang ceshi, 2020)
BACKGROUND Bauxite is often accompanied by useful components such as lithium, gallium, zirconium, and rare earth metals. Complete extraction and accurate determination of the content of these components are of great significance for the comprehensive evaluation and comprehensive utilization of bauxite resources. However, bauxite often contains a small amount of corundum, which is not completely decomposed by the conventional four-acid, five-acid and closure pressure acid dissolution methods, resulting in lower measurement results. OBJECTIVES To explore the new decomposition method to achieve rapid and accurate analysis of trace elements in corundum- bearing bauxite. METHODS A digestion technique using the solid compound ammonium bifluoride in a screw-capped PFA vial at high temperature has been developed for trace elements analysis of corundum-bearing bauxite by using a small amount of sulfuric acid during the fusion process. The factors such as different melting temperature, digestion time and reagent dosage were investigated in detail, the optimal smelting conditions (200℃, 3h, sample ratio 4:1) were confirmed. An analytical method for determination of 37 trace elements in corundum-bearing bauxite by inductively coupled plasma-mass spectrometry with rapid decomposition of ammonium bifluoride was established. RESULTS This method can be used to quickly and effectively decompose corundum-bearing bauxite, which has been verified by three national bauxite standard materials GBW07177, GBW07181 and GBW07182. The proposed method was also compared with the results of the four-acid, five-acid and closure pressure acid dissolution methods. The recoveries of nine elements such as Li, Ga, Sr, Zr and Pb in the three standard materials were from 95.0% to 115.0%, 90.0% to 110.0%, and 90.0% to 110.0%, respectively. The analytical result was in agreement with the certified values. The detection limits of the method were from 0.002 to 0.43μg/g, which was closely equivalent to the detection limits (0.000-0.48μg/g) of the traditional nitric acid-hydrofluoric acid closure digestion method. The precisions were from 1.14% to 8.84%, which qualified it to meet the analytical requirements of trace elements in bauxite. CONCLUSIONS This method can be used to achieve accurate analysis of major elements such as Al, Ti, and P in bauxite (Al2O3 content between 42.97% and 90.36%), which further verifies the accuracy of this method for the determination of trace elements in bauxite.